2021
DOI: 10.1155/2021/4868399
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Swimming Training Evaluation Method Based on Convolutional Neural Network

Abstract: By investigating the status quo of the swimming training market in a certain area, we can obtain information on the current development of the swimming training market in a certain area and study the laws of the development of the market so as to provide a theoretical basis for the development of the market. This paper designs an evaluation algorithm suitable for swimming training based on the improved AlexNet network. The algorithm model uses a 3 × 3 size convolution kernel to extract features, and the poolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…e results show that nearly half of the students' weight does not meet the standard, and through the operation results of the algorithm, it is observed that the students lack the training of lower limb strength in physical training, and the vital capacity grade and endurance grade are obviously weak. It is suggested that the students strengthen the training of aerobic exercise [10]. Zhang et al screened five strong association rules for boys and girls by using the association rule Apriori algorithm based on the body test data of college students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e results show that nearly half of the students' weight does not meet the standard, and through the operation results of the algorithm, it is observed that the students lack the training of lower limb strength in physical training, and the vital capacity grade and endurance grade are obviously weak. It is suggested that the students strengthen the training of aerobic exercise [10]. Zhang et al screened five strong association rules for boys and girls by using the association rule Apriori algorithm based on the body test data of college students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays, the recovery training for swimmers has become an indispensable part of the training, among which hyperthermia, massage, static stretching and related drug recovery are the most common means of recovery training. In addition, in the recent two years, the continuous improvement of psychological recovery training, nutritionist recovery and adjustment are effective means of recovery training [7].…”
Section: Recovery Trainingmentioning
confidence: 99%
“…The re projection error considers not only the calculation error of homography matrix, but also the measurement error of image points. In the homography transformation from the object plane to the image plane as shown in Figure 2, x is a point in the object plane, x′ is the corresponding point of x in the image plane, and the relationship between them should meets the relationship shown in the following equation [14].…”
Section: Pnp Problemsmentioning
confidence: 99%